"Beyond the Veil": The Antarctic Gothic Fictions of Poe, Verne, Leahy, Lovecraft, and Campbell - O'HARE, EDWARD REGINALD (Trinity College Dublin. School of English. Discipline of English, 2018)
The Antarctic has frequently been a location for Gothic narratives. Ever since Captain Cook declared that it was better for mankind not to know anything about the mysterious land which lay on the other side of the frozen Southern Ocean, the human imagination has been drawn to the far south. Samuel Taylor Coleridge set the key episode of his ?Rime of the Ancient Mariner? (1798) at the South Pole, but it was some of the earliest works of Edgar Allan Poe which established Antarctica as a Gothic setting. His short story ?MS. Found in a Bottle? (1833) and novel The Narrative of Arthur Gordon Pym of Nantucket (1838) were the first true Antarctic Gothic fictions. In this thesis, I argue that these works became the foundational texts of a subgenre which have depicted this geographical space as a realm of terror and wonder. Along with Poe, such authors as Jules Verne, H.P. Lovecraft, John W. Campbell, and a number of lesser known storytellers have used the Antarctic as a field of whiteness upon which to project their imaginative visions. In the first chapter I analyze the origins of Antarctica as a Gothic territory. Tracing the early history of South Polar exploration, I will discuss how the enigma surrounding this region stimulated a range of imaginative responses from writers who tried to envisage what this distant place must be like. Using the theories of Yi-Fu Tuan, I examine the Antarctic as an example of what he terms ?alien space,? an unnatural landscape which is an embodiment of Otherness. I then proceed to give a theoretical account of Gothic literature, describing its historical development and salient characteristics as a genre. Following this, I give a definition of the Antarctic Gothic subgenre. I then conclude this section by giving an overview of the previous research in this area and a short description of how Antarctica made the transition from an abstract concept to a speculative space to a geographical reality. The second chapter is devoted to an analysis of the central text of the Antarctic Gothic subgenre, Poe?s Arthur Gordon Pym. This chapter takes a range of approaches to this complex and deliberately ambiguous novel. I begin by assessing the developments in American scientific culture and imperial attitudes which heavily influenced Poe?s conception of the Antarctic. In particular, I discuss how Arthur Gordon Pym engages with the contemporary pseudoscientific theory of the ?hollow earth.? I then consider the Antarctic Gothic?s emergence from the subgenre of Gothic sea fiction. Lastly, I analyse the relationship between Arthur Gordon Pym and Poe?s earlier Antarctic Gothic narrative ?MS. Found in a Bottle,? before examining the novel?s mystifying closing polar episode. Jules Verne was a great admirer of Poe?s only novel, and the third chapter analyzes his own response to it, The Sphinx of the Ice Realm (1897). This chapter shall chart the origin of Verne?s interest in the Polar Regions and assess how he first explored this theme in his earlier novel The Adventures of Captain Hatteras (1866). This chapter then examines how Verne integrated the new discoveries which were being made by Antarctic explorers with his own speculative vision of this region, harkening back to Poe?s text in the process. Chapter four then focuses on the Heroic Age of Antarctic exploration, the period in which the exploration of the far south became a major cultural phenomenon. This chapter will give an account of both the discoveries and the disasters of this age, and consider how these were represented in Gothic fiction?s like John Martin Leahy?s ?In Amundsen?s Tent? (1928). H.P. Lovecraft?s At the Mountains of Madness (1936) is the subject of chapter five. Like Verne, Lovecraft was fascinated by the Antarctic and Poe?s Arthur Gordon Pym and both of these influences came together in his late novel. However, this chapter also analyses the diverse range of ideas he explores in Mountains of Madness. Questions of mankind?s past and future, and the terror of the unknown surface, as Lovecraft?s polar explorers make their way to the centre of the far southern continent. Chapter six analyses a different kind of Antarctic Gothic text, John W. Campbell?s ?Who Goes There?? (1938). This is a story which concentrates more on the nature of identity than the vast vistas of the white polar wastes, but is no less terrifying. I conclude this thesis by discussing some of the more recent examples of the Antarctic Gothic, and speculate how the subgenre may develop in the future.
APPROVED
Keywords: Gothic; Antarctica; Edgar Allan Poe; Jules Verne; John Leahy; H.P. Lovecraft; John W. Campbell, Jr